2016
DOI: 10.4238/gmr.15038629
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Mendelian inheritance, linkage, and genotypic disequilibrium in microsatellite loci of Hymenaea stigonocarpa Mart. ex Hayne (Fabaceae-Caesalpinioideae)

Abstract: ABSTRACT. Hymenaea stigonocarpa is a deciduous and monoecious Neotropical tree species pollinated by bats. Due to overexploitation and habitat destruction, the population size has drastically diminished in nature. No previous study has investigated Mendelian inheritance, linkage, and genotypic disequilibrium in the available microsatellite markers in this species. So, our aim was to estimate these parameters using six microsatellite loci in a sample of 470 adults and 219 juveniles from two populations of H. st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…DNA extraction from leaves of adult trees, juveniles, and germinated open‐pollinated seeds (offspring), amplification reactions, and microsatellite analysis procedures followed the methods described by Ciampi, Azevedo, Gaiotto, Ramos and Lovato () and Moraes and Sebbenn (). We used six dinucleotide microsatellite loci (Hc14, Hc17, Hc33, Hc39, Hc40, and Hc49), which were previous tested for our data (Moraes et al., ), for Mendelian inheritance and genetic linkage analyses based on the genotypes of the mother and open‐pollinated seeds, and for genotypic linkage disequilibrium based on the genotypes of adults and juveniles. The six loci present Mendelian inheritance, an absence of genetic linkage, genotypic linkage disequilibrium and high levels of polymorphism (Moraes et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA extraction from leaves of adult trees, juveniles, and germinated open‐pollinated seeds (offspring), amplification reactions, and microsatellite analysis procedures followed the methods described by Ciampi, Azevedo, Gaiotto, Ramos and Lovato () and Moraes and Sebbenn (). We used six dinucleotide microsatellite loci (Hc14, Hc17, Hc33, Hc39, Hc40, and Hc49), which were previous tested for our data (Moraes et al., ), for Mendelian inheritance and genetic linkage analyses based on the genotypes of the mother and open‐pollinated seeds, and for genotypic linkage disequilibrium based on the genotypes of adults and juveniles. The six loci present Mendelian inheritance, an absence of genetic linkage, genotypic linkage disequilibrium and high levels of polymorphism (Moraes et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…We used six dinucleotide microsatellite loci (Hc14, Hc17, Hc33, Hc39, Hc40, and Hc49), which were previous tested for our data (Moraes et al., ), for Mendelian inheritance and genetic linkage analyses based on the genotypes of the mother and open‐pollinated seeds, and for genotypic linkage disequilibrium based on the genotypes of adults and juveniles. The six loci present Mendelian inheritance, an absence of genetic linkage, genotypic linkage disequilibrium and high levels of polymorphism (Moraes et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant values were observed for different families and occurred more frequently between the following pairs: EMBRA2xEMBRA3, EMBRA2xEMBRA63, and EMBRA204xEMBRA128. The significant linkage may be the result of true genetic linkage or deviations from 1:1 Mendelian segregation (Manoel et al, 2015;Moraes et al, 2015), as observed for EMBRA2 and EMBRA63. The absence of linkage between the loci is important concerning models used in population genetic analyses, which assume random segregation between alleles of different loci.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to use molecular markers as genetic markers, it is important to determine whether their inheritance follows the rules of Mendelian segregation, and whether the loci are genetically linked (Tambarussi et al, 2013;Manoel et al, 2015;Moraes et al, 2016). Studies assessing linkage among loci are also necessary because the detected loci are used to calculate averages among loci in population genetic studies; therefore, linked loci can create bias in the estimates (Guidugli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%